Disruption of AtHAK/KT/KUP9 enhances plant cesium accumulation under low potassium supply. Issue 3 (26th August 2021) - Genies, Laure; Martin, Ludovic; Kanno, Satomi; Chiarenza, Serge; Carasco, Loïc; Camilleri, Virginie; Vavasseur, Alain; Henner, Pascale; Leonhardt, Nathalie
Abstract: Understanding the molecular mechanisms that underlie cesium (Cs + ) transport in plants is important to limit the entry of its radioisotopes from contaminated areas into the food chain. The potentially toxic element Cs +, which is not involved in any biological process, is chemically closed to the macronutrient potassium (K + ). Among the multiple K + carriers, the high‐affinity K + transporters family HAK/KT/KUP is thought to be relevant in mediating opportunistic Cs + transport. Of the 13 KUP identified in A. thaliana, only HAK5, the major contributor to root K + acquisition under low K + supply, has been functionally demonstrated to be involved in Cs + uptake in planta . In the present study, we showed that accumulation of Cs + increased by up to 30% in two A. thaliana mutant lines lacking KUP9 and grown under low K + supply. Since further experiments revealed that Cs + release from contaminated plants to the external medium is proportionally lower in the two kup9 mutant alleles, we proposed that KUP9 disruption could impair Cs + efflux. By contrast, K + status in kup9 mutants is not affected, suggesting that KUP9 disruption does not alter substantially K + transport in experimental conditions used. The putative primary role of KUP9 in plants is further discussed.